Awareness of National Health Insurance Scheme Activities and Service utilization Among Enrolled Employees in Government Institutions in Nigeria - Ironbar, Archibong E.; Agbor, Uno Ijim; Iji, Mary Eru (JINAV: Journal of Information and Visualization, 2021)
The study examined awareness of National Health Insurance Scheme activities and service utilization among enrolled employees in government institutions in Nigeria. Adopting the survey research method, data was collected from 1200 samples employed in three federal Government Institutions in Calabar, Cross River State, Nigeria using a structured self-developed questionnaire. The samples were selected using the purposive and proportional sampling technique. Descriptive analysis was used to present result and linear regression was used to check the variable under study at 0.05 confidence level. The result from the descriptive analysis revealed that there was moderate knowledge (48 per cent) that there are drugs not on the NHIS drug list. Result also revealed minimal knowledge (30 per cent) that there is some treatment not on the NHIS treatment List. Regression analysis revealed a moderate correlation (30 per cent) between awareness of NHIS activities and service utilisation (F (1, 1112) = 16.472; p < .000). The study concludes that there is moderate knowledge about the activities of the NHIS and this affects service utilization and satisfaction. The study recommends among others that the operators of the National Health Insurance Scheme should include more drugs on the prescription list to address the health needs of participants. The scheme should be expanded to cover all medical cases of enrollees. The government and the agencies in charge of the health insurance scheme should carry out periodic assessments of clients’ satisfaction with the scheme so as to make future policy decisions for better service delivery